The relationship between leadership and adaptive performance: A systematic review and meta-analysis. - Alice Bonini; Chiara Panari; Luca Caricati; Marco Giovanni Mariani (PLoS ONE)
This research presents a comprehensive review and meta-analysis of literature to examine the impact of various leadership styles on organizational adaptive performance (AP). AP is essential for job performance, especially in environments undergoing rapid changes. Previous reviews on AP found that transformational and self-leadership had had a positive influence on job adaptivity, while the relationship between other leadership styles and AP had not been clear. First, authors outlined the theoretical framework of AP and leadership, clarifying how job adaptivity and the different leadership styles are defined and discussed in the scientific literature. Subsequently four scientific databases were explored to identify studies that investigate the Leadership and AP' relationship. 32 scientific articles and 2 conference papers were investigated for review, of which 31 were used to conduct a meta-analysis; 52 different effect sizes from 32 samples were identified for a total sample size of 11.640 people. Qualitative synthesis revealed that the influence of different leadership styles on AP depended on contextual variables and on aspects related to the nature of the work. Moreover, it was found that leadership supported AP through motivational and relational aspects. Through this meta-analysis, it was found that a significant positive relationship between leadership and AP existed (Zr = .39, SE = .04, p < .001. 95%CI [.32, .47], r = .37). However, no differences emerged from the different leadership styles examined in the studies. This review deepens the importance of leadership as organizational factor that affect the employees' likelihood of dealing with continuously emergent changes at work, extended the search to emerging leadership approaches to highlight the value of collective contributions, ethics, and moral and sustainable elements that could positively affect AP.